RAHMAH EL YUNUSIYAH AND THE REFORM OF MUSLIM WOMEN’S EDUCATION IN MINANGKABAU (1922–1969) - Dwi Puji Lestari; Triwahana (CV. Fahr Publishing, 2026)
This study examines the role of Rahmah El Yunusiyah in reforming Muslim women’s education in Minangkabau between 1922 and 1969 by situating her contribution within the broader context of Islamic educational modernization in Indonesia. The research aims to analyze her socio-intellectual background, the institutional development of Diniyah Putri, and the structural impact of her educational model on women’s socio-religious roles. This study employs a historical research method, including heuristics (source collection), source criticism, interpretation, and historiography. Data were obtained primarily from written sources such as books, academic journals, theses, and archival materials, supported by limited observation and interviews. All sources were critically examined to ensure authenticity, credibility, and relevance. The findings indicate that Rahmah El Yunusiyah’s reform was rooted in her dissatisfaction with the co-educational system of Diniyah School, which inadequately addressed women-specific religious issues. In response, she established Al-Madrasah lil Banat (Diniyah Putri) in 1923 as a women-centered Islamic institution. Her educational model integrated religious sciences (fiqh, tauhid, hadith), general subjects, vocational training (weaving, sewing, midwifery), and a boarding school system to foster discipline and moral formation. This integrated system functioned as a strategic response to colonial educational dualism while maintaining Islamic epistemological foundations. The study concludes that Rahmah’s reform represented a holistic modernization project that repositioned Muslim women as “mother-educators” and intellectual agents, significantly contributing to the transformation of Islamic women’s education in Indonesia.